2007
DOI: 10.4319/lo.2007.52.1.0217
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of the “clearest” natural waters

Abstract: Optical measurements within both the visible and near ultraviolet (UV) parts of the spectrum (305-750 nm) were recently made in hyperoligotrophic waters in the South Pacific gyre (near Easter Island). The diffuse attenuation coefficients for downward irradiance, K d (l), and the irradiance reflectances, R(l), as derived from hyperspectral (downward and upward) irradiance measurements, exhibit very uncommon values that reflect the exceptional clarity of this huge water body. The K d (l) values observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
377
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(410 citation statements)
references
References 27 publications
19
377
1
2
Order By: Relevance
“…(13) (Ferrari and Tassan, 1992;Tassan 1994;Vodacek et al, 1997;Morel et al, 2007;Morel and Gentili, 2009;Bricaud et al, 2010;Organelli et al, 2014). We compared the a CDOM (λ)-Chl a relationship that we derived with some of the relationships between a CDOM (λ) and Chl a derived by various authors for different water types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(13) (Ferrari and Tassan, 1992;Tassan 1994;Vodacek et al, 1997;Morel et al, 2007;Morel and Gentili, 2009;Bricaud et al, 2010;Organelli et al, 2014). We compared the a CDOM (λ)-Chl a relationship that we derived with some of the relationships between a CDOM (λ) and Chl a derived by various authors for different water types.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships derived by other authors were found unsuitable for estimating CDOM absorption in the Baltic Sea and lake waters. The empirical relationships derived by Tassan (1994), Morel et al (2007), Morel and Gentili (2009) and Bricaud et al (2010) all underestimated CDOM absorption in the Baltic Sea. Such a great discrepancy between estimated and observed CDOM absorption values has resulted from the fact that these relationships were developed for clear oceanic waters, where the contribution of dissolved organic material to the total light absorption was less than in the Baltic Sea and the concentration of Chl a did not exceed 40 mg m −3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presented simulations are carried out for perpendicular solar irradiation and for an extreme clear atmosphere, where the diffuse skylight due to atmospheric Rayleigh and Mie scattering accounts for 10 % only (the sky illumination is assumed to be isotropic). The water body under consideration is very clear and oligotrophic; the (wavelengthdepending) inherent optical properties of the well-mixed seawater are derived from a chlorophyll a concentration Chl of 0.1 mg m −3 (Morel et al, 2007;Morel, 2009). The resulting diffuse attenuation coefficient for the downward irradiance K d (490 nm) is approximately 0.038 m −1 , relating to a flat sea surface.…”
Section: Model Input Parametersmentioning
confidence: 99%